Comparative morphological analysis of male reproductive structures of Orthopterygium and Amphipterygium genera, (Anacardiaceae) - Jimenez-Vasquez, Victor (2017)
We present a descriptive study on the male inflorescence and flowers of the genus Orthopterygium (A. Gray) Hemsl. in comparison with their sister genus Amphipterygium Standl., formerly recognized as Julianiaceae, with the aim of corroborate their current taxonomic status. We included all species of both genera O. huaucui, A. adstringens, A. molle, A. simplicifolium and A. glaucum. We measured floral pieces (flower length, sepal length, anther length and filament length) and inflorescence. These data were compared in a principal component analysis. Sepals length and sepals number are the most significant discriminant characters between both genera. This work supports and corroborates the results obtained by other authors and comprises the first initiative on the evaluation of the actual taxonomic status of Orthopterygium and establishes the distinction of both genera as independent entities.